The genus Prestonia (Apocynaceae) in Colombia - Morales, J. Francisco; Liede-Schumann, Sigrid (Phytotaxa, 2016)
A treatment of Prestonia in Colombia is presented, including a key to the 25 species, descriptions, distribution data, and selected specimens examined. Prestonia megagros is reported for the country for first time, and conversely, P. surinamensis is excluded. Prestonia antioquiana is newly described and ilustrated. A lectotype is designated for Echites megagros.